Phase-field simulations of curvature-induced cascading of Widmanstätten-ferrite plates. (15th January 2017) - Bhattacharya, Avisor; Ankit, Kumar; Nestler, Britta
Abstract: In the present study, we employ a multiphase-field model based on the grand chemical potential formulation to simulate the morphological evolution of secondary Widmanstätten ferrite ( α ') during isothermal γ (austenite) → α ' transformation in binary Fe-C steels. We add the stored-energy to the free-energy data obtained from CALPHAD database to simulate realistic kinetics of α ' plates in diffusion-controlled regime. By implementing an elliptic anisotropy in the interfacial energy, we study the influence of supersaturation on the growth kinetics and stable morphologies of the single plate and colonies while scrutinising the conformity of numerical simulations with theory. For the first time, we elucidate the curvature-driven mechanism by which, a cascade of parallel offspring plates evolve adjacent to the parent sideplate. The present phase-field simulations, while providing significant insights into the curvature-induced mechanism of evolution of α ' colony, also close the gap with in-situ observations reported earlier. Graphical abstract: Image 1